2008
DOI: 10.5713/ajas.2008.60322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy Concentration and Lysine on the Digestible Energy Ratio for Apparent Amino Acid Digestibility in Finishing Barrows

Abstract: This experiment was performed to investigate the effects of two energy levels and four lysine:digestible energy (DE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Therefore, essential amino acid digestibility data are presented and discussed, whereas the nonessential amino acid data were excluded. In this study, increasing Lys concentration significantly increased the Arg, His, Met, Lys, Thr and total essential amino acid digestibility during the first 7 days, Similarly, Cho et al . (2008) also demonstrated the higher apparent digestibility of all amino acids except for leucine, proline, alanine and tyrosine with increasing Lys levels.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, essential amino acid digestibility data are presented and discussed, whereas the nonessential amino acid data were excluded. In this study, increasing Lys concentration significantly increased the Arg, His, Met, Lys, Thr and total essential amino acid digestibility during the first 7 days, Similarly, Cho et al . (2008) also demonstrated the higher apparent digestibility of all amino acids except for leucine, proline, alanine and tyrosine with increasing Lys levels.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it is well known that higher energy levels require higher amino acid levels in diets, since feed intake will be decreased by increases in the diet. Cho et al . (2008) also suggested that maintaining the appropriate lysine : energy ratio is very important as the energy density of the diet increased.…”
Section: Discussionmentioning
confidence: 99%
“…The oil content of the high nutrient density diet was about 51 g kg −1 while the low density diet contained soybean oil at less than 6 g kg −1 . A higher energy content of the diet improves fat digestibility too . So, a higher fat content and a higher fat digestibility of a high nutrient density diet results in the better performance of the chickens that received the high nutrient density diet.…”
Section: Resultsmentioning
confidence: 99%
“…A higher energy content of the diet improves fat digestibility too. 23 So, a higher fat content and a higher fat digestibility of a high nutrient density diet results in the better performance of the chickens that received the high nutrient density diet. Similarly, it has been reported that increased nutrient density increased weight gain and improved feed conversion ratio in growing pigs and suggested it was significantly associated with improved feed intake, which may explain the increased growth performance in the present study too.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have been conducted using variable ratios of lysine to energy [ 1 ]. Cho et al [ 5 ] observed that the best lysine to digestible energy (DE) ratio for maximum amino acid digestibility of the pig is 2.4 g total lysine/Mcal DE for barrows (Landrace × Yorshire × Duroc; 64 kg). Chang et al [ 6 ] showed that the optimal lysine to DE ratios were 3.2 and 3.8 g total lysine/Mcal DE for barrows and gilts (Landrace × Yorshire × Duroc; 16 to 57 kg), respectively.…”
Section: Introductionmentioning
confidence: 99%